KEPASTIAN HUKUM AKTA PERJANJIAN KERJASAMA ANTARA PEMERITAH DKI JAKARTA DENGAN PIHAK PENGEMBANG TERKAIT PEMENUHAN KEWAJIBAN FASILITAS SOSIAL DAN FASILITAS UMUM YANG TELAH DISETUJUI DALAM SURAT IZIN PENUNJUKAN PENGGUNAAN TANAH (SIPPT). - Kurniawan, Iwan; Marniati, Felicitas Sri; Irhamsah, Irhamsah (LPPM Institut Pendidikan Nusantara Global, 2024)
Legal certainty regarding the Deed of Cooperation Agreement between the Regional Government of DKI Jakarta and the Developer regarding providing social and public health obligations in the Land Use Designation Letter (SIPPT), has been regulated in the Civil Code and DKI Jakarta Regional Regulation Number 7 of 2002 concerning Public Infrastructure, Facilities and Utilities, but it has been implemented what happens is not fulfilling its obligations. The formulation of the problem in this research is how the authority of the Regional Government of DKI Jakarta is related to the non-fulfillment of social and social infrastructure obligations in the SIPPT by the floating party, and how is the legal certainty of the deed of cooperation agreement between the Regional Government of DKI Jakarta and the relevant Floating Party containing the social and public welfare obligations in the SIPPT. Legal theories used in this research: Authority Theory according to Bagir Manan and Legal Certainty Theory according to Gustav Radbruch. The method used in this research is a type of normative juridical research, namely legal library research or secondary data with primary, secondary and tertiary sources of legal materials. The research approaches used are the Legislative, Conceptual, Case and Analytical Approaches and techniques for collecting legal materials are carried out by identifying and inventorying positive legal rules, literature books, journals and other sources of legal materials. The analysis technique for legal materials is carried out using Grammatical Interpretation and Systematic Interpretation. The results of this research indicate that the DKI Jakarta Government has the authority to collect, supervise, prohibit, complete maintenance, provide administrative sanctions and criminal sanctions for providing social and public health obligations to developers in accordance with DKI Jakarta Regional Regulation Number 7 of 2002 concerning Public Infrastructure, Facilities and Utilities. The commitment and professionalism of DKI Jakarta Regional Government officials to carry out their authority by providing strict sanctions to developers who do not carry out their obligations. Legal certainty regarding the deed of cooperation agreement between the DKI Jakarta Government and the Developer regarding social and public facilities obligations in accordance with the Land Use Designation Permit (SIPPT), has legal certainty in accordance with the Pacta Sunt Servanda Principle where the agreement is valid as law for the party making it. Changes to the agreement are possible as long as both parties agree to it in the form of an addendum to the agreement, however non-implementation of the agreement is a breach of contract which can be sued in court.